Effect of sub-lethal concentrations of insect growth regulator, lufenuron on larval growth and development of Aedes aegypti - Salokhe, S. G.; Mukherjee, Samindra N.; Deshpande, S. G.; Ghule, V. P.; Mathad, J. R. (Current Science, 2010)
The effect of sub-lethal concentrations (LC20 = 0.0002 and 0.001 ppm, and LC40 = 0.002 and 0.02 ppm for II and IV instar larvae respectively) of a dispersible concentrate formulation of the insect growth regulator, lufenuron on larval growth and development of Aedes aegypti was studied. When II and IV instar larvae were subjected to the above-mentioned sub-lethal concentrations of lufenuron through the culture medium, there was a significant increase in the time taken for pupation (17.2 +/- 0.74 and 11.4 +/- 0.8 days for II and IV instar LC20-treated larvae respectively, and 19 +/- 0.89 and 14.6 +/- 1.0 days for II and IV instar LC40-treated larvae respectively). Also, there was increase in the time taken for adult emergence 3.8 +/- 0.83 and 5.4 +/- 0.83 days from pupation of LC40-treated II and IV instar larvae respectively). There was 28.1 +/- 2.06% and 43.59 +/- 0.87% reduction in pupation in LC20 of lufenuron-treated II and IV instar A. aegypti larvae respectively. Also, with LC20 of lufenuron-treated II and IV instar larvae there was 43.54 +/- 5.12% and 43.59 +/- 0.87% reduction in adult emergence respectively. Further, it was observed that II instar larvae treated with LC20 of lufenuron developed into 25.8 +/- 2.08% deformed adults. In LC40-treated II instar larvae there was 33.72 +/- 2.38% reduction in pupation and 63.44 +/- 4.76% reduction in adult emergence. Also, it was observed that there was 54.84 +/- 3.9% and 61.3 +/- 5.2% reduction in pupation and adult emergence respectively, in IV instar larvae treated with LC40 of lufenuron. The reduction in pupation of the IV instar larvae treated with LC40 of lufenuron was due to failure of the larvae to undergo pupation. These studies are fundamental to the use of lufenuron in A. aegypti management.
Keywords: Aedes aegypti; larval growth and development; lufenuron; sub-lethal concentration

Evaluation of the insect growth regulator lufenuron (MatchA (R)) for control of aedes aegypti by simulated field trials - Salokhe, S. G.; Deshpande, S. G.; Mukherjee, Samindra N. (Parasitology Research, 2012)
The insect growth regulator, Lufenuron, at concentrations of even multiples of LC90 (determined under laboratory conditions) was tested against the III instar larvae of Aedes aegypti under simulated field conditions. For all concentrations tested, 100 % mortality of the larvae was observed within 24 h of exposure to Lufenuron-treated water. In experiments with LC90 x 4 Lufenuron concentration and where 15 % of water volume was replaced daily, percent mortality of the larvae was reduced to 40 % after the 54th day of treatment. Percentage mortality of the III instar larvae on the 54th day was higher in water with LC90 x 6 concentration than that observed for water with LC90 x 4 of Lufenuron. In the experiments with LC90 x 4 and LC90 x 6 concentrations of Lufenuron where 15 % of water volume was replaced weekly, larval mortality obtained after the eighth week was 68.75 and 88.33 %, respectively. In LC90 x 4 and LC90 x 6 of Lufenuron-treated stagnant water (without replacement of water), the percent mortality of the larvae on the 55th day was 65 and 90 %, respectively. Introducing a fresh batch of III instar A. aegypti larvae in the Lufenuron-treated waters revealed that residual activity of Lufenuron was sustained for 45 days after the treatment. All these experiments revealed that Lufenuron not only affects the prevalence of the A. aegypti larvae but also induces the development of abnormal adults.